Review of autoinflammatory diseases, with a special focus on periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis syndrome. (19th August 2016) - Wekell, Per; Karlsson, Anna; Berg, Stefan; Fasth, Anders
Abstract: There have been remarkable developments in the field of autoinflammatory diseases over the last 20 years. Research has led to definitions of new conditions, increased understanding of disease mechanisms and specific treatment. The polygenic autoinflammatory condition of periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) is the most common autoinflammatory disorder among children in many parts of the world. The clinical features often include clockwork regularity of episodes, prompt responses to corticosteroids and therapeutic effects of tonsillectomy, but the disease mechanisms are largely unknown. Conclusion: This review discusses the emerging understanding of autoinflammatory diseases, with special emphasis on PFAPA.